2015
DOI: 10.1152/ajpregu.00418.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal stress affects the aging trajectory of female rats on the endocrine, temperature, and ventilatory responses to hypoxia

Abstract: Human and animal studies on sleep-disordered breathing and respiratory regulation show that the effects of sex hormones are heterogeneous. Because neonatal stress results in sex-specific disruption of the respiratory control in adult rats, we postulate that it might affect respiratory control modulation induced by ovarian steroids in female rats. The hypoxic ventilatory response (HVR) of adult female rats exposed to neonatal maternal separation (NMS) is ∼30% smaller than controls (24), but consequences of NMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 71 publications
(115 reference statements)
0
21
1
Order By: Relevance
“…However, OVX animals had lower a ventilatory response to hypoxia than cycling rats in estrous. Fournier et al [17] showed that rats with reduced circulating levels of ovarian hormones (whether by ovariectomy or aging) had reduced hypoxic ventilatory responses when compared to young intact females. This result is in agreement with the findings of the present study, suggesting that ovarian hormones play a role in the ventilatory control system, providing an important signal that drives breathing.…”
Section: Discussionmentioning
confidence: 99%
“…However, OVX animals had lower a ventilatory response to hypoxia than cycling rats in estrous. Fournier et al [17] showed that rats with reduced circulating levels of ovarian hormones (whether by ovariectomy or aging) had reduced hypoxic ventilatory responses when compared to young intact females. This result is in agreement with the findings of the present study, suggesting that ovarian hormones play a role in the ventilatory control system, providing an important signal that drives breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Nonseparated control animals (CTRL) were continuously maintained under standard animal care procedures throughout the neonatal period with minimal human intervention. Because short periods of handling has distinct effects on HPA development, these animals are the most desirable control group for investigations of the effects of NMS on central nervous system development . On postnatal day 21, rats were weaned and housed two per cage under standard animal care conditions until adulthood (8‐10 weeks old), at which time the ventilatory measurements were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Ventilation was measured in unrestrained and awake rats using a whole‐body, flow‐through plethysmograph (PLY3223; Buxco Electronics, Sharon, CT, USA) as reported previously . Briefly, the system consists of a 2‐L Plexiglas experimental chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Two days after delivery, litters were culled to 12 pups, when necessary, with a roughly equal number of males and females. The NMS protocol was identical to the one used in previous studies (Genest et al, 2004 ; Fournier et al, 2015 ). Briefly, the entire litter was separated from their mother for 3 h/day (09.00–12.00 h) from post-natal days 3 to 12.…”
Section: Methodsmentioning
confidence: 99%